ID 366 – Cerebral venous thrombosis (CVT) in a female patient with severe obstructive sleep apnea (OSAS): Case presentation. Issue 3 (March 2016) - Rashed, H.; Marei, A.; Tork, M.; Abdelnasser, A.
Abstract : Objectives: Obstructive sleep apnea syndrome is reported to be a risk factor for arterial ischemic stroke, however, relationship between OSAS and cerebral venous thrombosis (CVT) remains uncertain. Case presentation: We present a case of a 38-year-old obese woman, who developed headache, seizures and hemiparesis. Patient was taking combined oral contraceptive pills (OCPs) for 2 weeks prior to this event. Her coagulation profile (including ANA, anti dsDNA, antithrombin III, protein C and S and factor V leiden) was unremarkable. Magnetic resonance imaging (MRI) brain and magnetic resonance venography (MRV) were done and showed CVT. Patient underwent an overnight polysomnogram (PSG) which revealed severe OSAS. Conclusion: Inspite of being a risk factor for venous thrombosis, short term consumption of OCPs cannot be considered as the only risk factor for the development of CVT in this patient, especially in the absence of hereditary thrombophilic state. In this obese patient, severe OSAS may be considered as another relevant contributory factor, which, together with the short term OCPs consumption, predisposes the patient to a state of hypercoagulability. Thus, OSAS should be considered as one of the multiple factors causing CVT.